2016
DOI: 10.1177/0022034516629119
|View full text |Cite
|
Sign up to set email alerts
|

Plasma of Argon Affects the Earliest Biological Response of Different Implant Surfaces

Abstract: The aim of this in vitro study was to evaluate the early cell response and protein adsorption elicited by the argon plasma treatment of different commercially available titanium surfaces via a chair-side device. Sterile disks made of grade 4 titanium (n= 450, 4-mm diameter) with 3 surface topographies (machined, plasma sprayed, and zirconia blasted and acid etched) were allocated to receive 4 testing treatments (2% and 10% protein adsorption and cell adhesion with MC3T3-E1 and MG-63). Furthermore, the specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 46 publications
11
87
0
Order By: Relevance
“…In vitro studies have demonstrated that plasma of argon treatment can activate the surfaces at the atomic and molecular levels, preserving the integrity of the titanium surface (Canullo et al. ). This activation enhances the activity of bone‐forming cells at the tissue–implant interface (Canullo et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have demonstrated that plasma of argon treatment can activate the surfaces at the atomic and molecular levels, preserving the integrity of the titanium surface (Canullo et al. ). This activation enhances the activity of bone‐forming cells at the tissue–implant interface (Canullo et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, dental implants able to improve the soft tissue attachment and osseointegration are being actively pursued (Seon et al 2015;Canullo et al 2016a). In vitro studies have demonstrated that plasma of argon treatment can activate the surfaces at the atomic and molecular levels, preserving the integrity of the titanium surface (Canullo et al 2016b). This activation enhances the activity of bone-forming cells at the tissue-implant interface (Canullo et al 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of previous studies 8, 24, 31 , we used at least four samples in each experiment, repeating each experiment three times. We analysed the results obtained for the three groups at each time point by means of one-way analysis of variance (ANOVA) using Tukey’s method.…”
Section: Methodsmentioning
confidence: 99%
“…In this contest, atmospheric pressure plasma treatment (APP) was demonstrated to increase the surface energy producing hydrophilic surfaces and enhancing their wettability . Additionally, APP treatment could activate surfaces at the atomic and molecular level, promoting protein adsorption and cell spreading …”
Section: Introductionmentioning
confidence: 99%